Implicações do teletrabalho nas relações trabalho-família: um olhar multifocal de profissionais de tecnologia durante a pandemia da covid-19 - Oliveira, Rafael Ribeiro (2023)
With the advent of Covid-19 pandemic, institutions and individuals have forcibly migrated to teleworking, creating a total disruption about how people work and perceive their workplace. Men and women began to work from home, significantly altering the temporal and spatial boundaries between paid work and domestic work. This study aimed to analyze the experiences of technology professionals about the implications of teleworking on the work-family relationship from the advent of the Covid-19 pandemic.. The theoretical background addressed concepts related to disruptive events, VUCA world, telework, and the following conceptions in understanding the work-family relationship: conflict, boundary, enrichment, integration, and the notion of life-work continuum. The research was conducted using a qualitative approach, through basic qualitative research. Data collection occurred through the use of semi-structured interviews. Thirteen professionals, married with children, seven men and six women, participated in the research. The data analysis used the steps of the comprehensive interpretive analysis. The results made it possible to understand Covid-19 as a disruptive phenomenon in the view of these professionals. This period was marked by the compromising of the social dimension of work, strategies initially based on improvisation, flexibility of space and time, fragmentation in the execution of the exercise of roles, negative feelings, and impacts on the family context, such as changes in routine and intensification of relationships. Besides this, impacts were observed in all the contexts experienced by these individuals. From the professional perspective, negative aspects emerged related to social isolation, fear concerning job permanence, work overload, and fragmentation of activities. On the other hand, positive attributes related to flexible schedules, more autonomy, and focus on the accomplishment of activities also emerged. From the family perspective, the impacts are related to the greater participation in domestic activities and childcare and the increase in the number of conflicts, the latter a consequence of the intensification of relationships. Under the individual conception, it was observed characteristics in opposite direction linked to the adoption of self-care practices versus the break of healthy routine. Regarding the conception of the relationship between work and other spheres of life, it was found that the absence of physical boundaries was the main reason for conflict, added to the uncertainties of the confinement period and the compulsory adaptation to teleworking. In this process, all individuals recognize that working from home, somehow, enriched the performance of one another role and, considering the experiences lived during the pandemic, new visions about the relationships of work and other spaces of life were being built, such as the perspective of integration and life-work continuum. The results contributed to broaden the discussions about how the different experiences of teleworking in the pandemic enabled the redefinition of ideas and new perceptions related to work relationships and other spaces of life.